2018
DOI: 10.1515/dema-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

The group of diffeomorphisms of a non-compact manifold is not regular

Abstract: We show that a group of diffeomorphisms D on the open unit interval I, equipped with the topology of uniform convergence on any compact set of the derivatives at any order, is non regular: the exponential map is not defined for some path of the Lie algebra. this result extends to the group of diffeomorphisms of finite dimensional, non compact manifold M. MSC(2010): 22E65; 22E66.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…In this paper, we have discussed diffeological Lie groups, and it is natural to ask whether they are regular. J-P. Magnot [Mag17] has shown that this is not the case. So we need to investigate further if regular diffeological Lie groups can be classified.…”
Section: Remarksmentioning
confidence: 98%
“…In this paper, we have discussed diffeological Lie groups, and it is natural to ask whether they are regular. J-P. Magnot [Mag17] has shown that this is not the case. So we need to investigate further if regular diffeological Lie groups can be classified.…”
Section: Remarksmentioning
confidence: 98%
“…One then can consider "natural" notions of smoothness, inherited from the embedding into Cl(S 1 , V ) for the pseudo-differential part, and from the well-known structure of ILB Lie group [31] from the diffeomorphism (phase) component. In order to be more rigorous, one can then consider Frölicher Lie groups along the lines of [23,25] in this context, or in [24,27] when dealing with other examples where this setting is useful. A not-so-complete description of technical properties of Frölicher Lie groups can be found in works by other authors [16,29,30] but this area of knowledge, however, still needs to be further developed.…”
Section: The Mapsmentioning
confidence: 99%
“…On a finite dimensional manifold M, the Lie algebra of the ILH Lie group of diffeomorphisms [36], defined as the tangent cone at the identity map, is the space of smooth vector fields, i.e. smooth sections of T M. On a non-compact, locally compact manifold, the situation is quite similar [32] while the group of diffeomorphisms is no longer a Fréchet manifold but a Frölicher Lie group. On these groups, the underlying diffeology is the functional diffeology, as well as for the more general definition of Dif f (X) when X is a diffeological space [21].…”
Section: Tangent Spaces Diffeology and Group Of Diffeomorphismsmentioning
confidence: 99%